Characterisation of T cell specificity, functional, activation and memory profiles associated with QuantiFERON TB Gold conversion and reversion - Mpande, Cheleka Anne-Marie (Department of Pathology, 2022)
Recent acquisition of Mycobacterium tuberculosis (M.tb) infection is associated with a higher risk of tuberculosis disease, compared with remote, asymptomatic infection. M.tb infection, defined by a positive tuberculin skin test (TST) and/or IFN--release assay [IGRA e.g. QuantiFERON TB GOLD (QFT)], is commonly thought to be a chronic state. However, longitudinal studies have demonstrated the dynamic nature of M.tb infection, whereby TSTs and IGRAs revert from a positive to a negative test in some individuals, possibly an indication of bacterial clearance. Despite the first observation of discordant serial TST results over 80 years ago and the wide use of TSTs/IGRAs, there is still a limited understanding of immunological features associated with different stages of M.tb infection and discordant serial TST/IGRA results. Most studies of M.tb-specific immune responses in humans are based on cross-sectional comparisons between M.tb infection and active disease, with very few large cohort studies enabling a longitudinal assessment of different phases of infection. Thus, the main objective of this thesis was to gain a better understanding of changes in M.tbspecific CD4 T cell functional, memory and activation profiles associated with QFT conversion (acquisition of M.tb infection) and reversion (potential M.tb clearance). Our first aim was to characterise the homing, cytotoxic and functional capacity of M.tbspecific memory CD4+ T cells during recent and remote M.tb infection, with a special focus on stem cell memory T (TSCM) cells. TSCM cells play a critical role in maintaining long-lasting immunity, demonstrated by their superior longevity, proliferation and differentiation capacity compared to central memory (TCM) and effector (TE) cells. Before this study, our knowledge of TSCM cells was primarily based on virus-specific CD8+ TSCM cells. We demonstrate that M.tb-specific CD4+ TSCM cells are induced upon recent M.tb infection and maintained at steady-state during established infection. Despite being the least differentiated M.tb-specific memory subset and representing 2 years) M.tb infection, we also aimed to define an M.tb- specific T cell biomarker that can distinguish between the two infection states as current diagnostics fail to do so. Our second major finding demonstrated that recently infected individuals have lower proportions of highly differentiated IFN-+TNF+KLRG-1+ CD4+ TE cells and higher proportions of early differentiated IFN--TNF+IL2+KLRG-1- CD4+ T cells than remotely infected individuals in response to M.tb lysate but not CFP-10/ESAT-6 stimulation. Akin to their recent M.tb exposure, recently infected individuals had higher levels of T cell activation, regardless of M.tb antigen specificity, than remotely infected individuals. The degree of M.tb-specific CD4 T cell activation was identified as the best candidate biomarker for recent infection. The very same biomarker could also distinguish between progressors and non-progressors and identify individuals with active tuberculosis disease among healthy individuals with remote M.tb infection. We propose that, upon large-scale clinical validation, the T cell activation biomarker could be used as a screening test in conjunction with current tuberculosis diagnostics to guide the provision of either preventive or full tuberculosis therapy. These results have very important implications for targeting provision of preventive treatment to M.tb infected individuals at high-risk of tuberculosis, which is one of the top 10 strategies required to achieve tuberculosis elimination targets. Based on data from observational studies conducted during the pre-antibiotic era and guinea pig tuberculosis models, TST/IGRA reversion in humans is hypothesised to be associated with spontaneous (natural) clearance of infection. Similarly, individuals recently exposed to patients with tuberculosis who did not convert TST/IGRA (termed resistors) nor develop disease had M.tb-specific T cell responses that did not include IFN- production. However, clearance of M.tb infection is virtually impossible to demonstrate in healthy individuals. We clearly illustrated that acquisition infection is associated with induction of CD4+ Th1 functional and memory T cell subsets associated with increased antigen burden. We thus hypothesised that if reversion represents natural M.tb infection clearance then immune responses post-QFT reversion, if detectable, would be predominantly TSCM/TCM cells that have an IFN- independent cytokine expression profile and low T cell activation levels. Interestingly, QFT reversion was not associated with a decrease in CFP-10/ESAT-6-specific IFN-+ CD4 T cell responses detected by flow cytometry. Overall, CD4 T cell responses to CFP-10/ESAT-6 in reverters were of intermediate magnitude between non-converters and remotely infected individuals. These responses were very low in most reverters (regardless of QFT status), which may explain fluctuations around the QFT assay cut-off resulting in reversion of the test. In the reverters who had low but robustly detectable responses, CFP-10/ESAT-6-specific CD4 T cells showed low levels of M.tb-specific T cell activation, maintenance of both IFN- dependent and independent Th1 cytokine co-expressing profiles and a predominantly TTM/TE phenotype. Memory and functional profiles detected in reverters in response to M.tb lysate shared more characteristics with non-converters than persistently infected (QFT+) individuals. Based on these results, we conclude that QFT reverters represent a heterogenous population in the tuberculosis spectrum who may experience very low or no in vivo antigen exposure. Altogether, these results indicate that not everyone with a QFT+ test likely experiences ongoing in vivo M.tb exposure, as suggested by much lower T cell activation observed during remote M.tb infection and QFT reversion compared to recent M.tb infection. Whether ongoing in vivo antigen exposure is required to maintain memory responses against M.tb remains to be determined. It is possible that key features of T cell responses against M.tb, including magnitude and differentiation, are shaped by the antigen load experienced during primary infection, regardless of whether infection is subsequently cleared. Answering these questions is critical to inform the interpretation of the current immunodiagnostic assays and to determine who could be spared from preventive tuberculosis therapy. On the other hand, here we defined a biomarker of recent infection and tuberculosis disease, which could enable the provision of targeted treatment to those who would benefit the most.